A history of the Middle East - Friedman, Saul S., 1937-2013. (Jefferson, N.C. : McFarland & Company, Inc., Publishers, 1981)
"This history covers the Middle East from its ancient beginnings to the present. The Byzantine and Ottoman empires, which laid much of the framework for the region to move into the modern era, are covered in depth, as are World Wars I and II and the regional conflicts that inflame the Middle East of the 21st century"--Provided by publisher.
An introduction to the Middle East -- The dry land -- The blessings of oil -- The cradle of civilization -- Foundations of the Bible -- The origins of law and war -- Ancient Persia: stability through good government -- The age of wonder: Greeks, Romans, Carthaginians -- The Jews: historic roots and definitions -- The Jews and their culture -- Judaism and Christianity -- The Byzantine Empire -- The Arabs and their culture -- Muhammad -- The teachings of Islam -- The Islamic schism -- Expansion of Islam -- Al-amjad: the Abbasid Caliphate -- The Crusades -- Mamelukes, Mongols, and Delhi sultans -- The Ottomans -- Ottoman decline -- World War I -- Republican Turkey -- The renaissance of Arab nationalism -- Political Zionism -- The Middle East between World Wars -- World War II -- Postwar Palestine: two refugee questions -- Egypt: Nasser's philosophy of revolution -- Egypt: Sadat and Mubarak -- Israel and the Palestinians -- Lebanon: good intentions gone awry -- Modern Iran -- The radical Arab states -- The Middle East in the 21st century.
Includes bibliographical references (p. 331-334) and index.
Keywords: Middle East -- History